Pemberdayaan Masyarakat terhadap Pemanfaatan Pupuk Organik Cair untuk Tanaman Padi di Desa Palasari: - - KKN 130 Bhakti Ananta, Fitri Laelatul (Sinesia : Jurnal Pengabdian Masyarakat, 2025)
Empowerment of farming communities aimed at farmers in Palasari Village, Legok District, Tangerang Regency is a community service program supported by LPPM Syarif Hidayatullah State Islamic University, Jakarta. The long-term goal of this program is for farmers to cultivate rice organically. By implementing organic methods, farmers are not only expected to be able to increase production yields, but also achieve farming sustainability, independence, product competitiveness, bargaining power, and a positive impact on the environment. However, to achieve this goal, the initial challenge faced was the low skills of farmers in making Liquid Organic Fertilizer (POC). The solution to overcome this problem is through training in making liquid organic fertilizer. This fertilizer is made by utilizing natural resources available around the village. Through this empowerment activity, farmers in Palasari Village are expected to become more skilled and capable